University Social Responsibility: the case of the Spanish Universities: Tools for their communication - González Alcántara, Óscar Jesús; Fontaneda González, Ignacio; Camino López, Miguel Ángel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Year after year, University Social Responsibility (USR) is gaining importance in universities. A study is presented to review the situation of Spanish universities that carry out USR in 2020 and its evolution over 10 years. Firstly, the concept of USR is reviewed and a definition is proposed, followed by an exploratory study in search engines, directories and university websites that analysis typology, stakeholders or the organizational structure to manage USR, as well as showing how communication and published reports of Social Responsibility are carried out.